هاتنهناوەوەى فهلسهفه بۆ ناو شارستانییهتى ئیسلاميی له ڕێگای وەرگێڕانهوە ( - الدین, عطا عبدالرحمن محي; حمهرشید, مهریوان عهبدول عبداهلل (Sulaimani Journal for Humanities, 2021)
In the Islamic civilization, the translation movement began before the Abbasid Caliphate, but in the era of the Abbasid Caliphate it expanded into and included many fields. One of the most important fields that arose from the translation movement and developed in this civilization was philosophical thought. It was thanks to translation philosophy entered the Islamic world. There are many different reasons that motivated the translation of philosophy, including: the Islamic conquests and the expansion of this civilization from a geographical area. The keenness and support of the Abbasid caliphs. From them, Islamic civilization was in dire need of logic and philosophy at the time and used in logical and philosophical debates, arguments, etc. There are a group of skilled and renowned translators who did the philosophical translation, many of whom were Christians or other religions, They were able to translate an important part of the Greek philosophy books from Syriac and Greek into Arabic, most notably Plato and Aristotle.